VIRTUAL METHODIC OFFICE - Igor V. Riatshentcev; Viacheslav A. Starodubtsev (Открытое образование (Москва))
The article considers the possibility of virtual methodic offices to support continuous professional development and self-education. A structural model of a virtual methodic office and the comparisons with collective and individual blogs are discussed.